Successful Endoscopic Treatment of Bouveret Syndrome in a Patient with Choledochoduodenal Fistula Complicating Duodenal Ulcer - Syed Hasan; Zubair Khan; Umar Darr; Toseef Javaid; Nauman Siddiqui; Jamal Saleh; Abdullah Kobeissi; Ali Nawras (Case Reports in Gastrointestinal Medicine)
Introduction. Cholecystoduodenal fistulas represent the most common type of bilioenteric fistulas while choledochoduodenal fistulas account for only 1–25% of cases. Bilioenteric fistula cases are associated with cholelithiasis and are rarely associated with duodenal peptic ulcers. Here we present the first case of Bouveret syndrome secondary to choledochoduodenal fistula complicating peptic duodenal ulcer managed successfully via endoscopic mechanical lithotripsy. Case. 86-year-old male with a medical history significant for coronary artery disease and stage 3 colorectal cancer status after resection and chemoradiation presented with intractable sharp abdominal pain worse postprandially for one week in duration, associated with early satiety, anorexia, and 5 lbs weight loss in one week. CT abdomen showed possible choledochoduodenal fistula and a distended stomach. An esophagogastroduodenoscopy (EGD) was performed revealing a large 2.5–3 cm stone lodged in the duodenal bulb at the base of duodenal ulcer with a fistula opening beneath it. The stone was extracted in 2 pieces via mechanical lithotripsy. Endoscopic ultrasound of the CBD revealed Rigler’s triad. Conclusion. Bouveret syndrome is mostly associated with cholecystoduodenal fistula and has high mortality and morbidity due to underlying comorbid conditions and elderly age. Patients are not always fit for surgical management, and endoscopic management is not always successful.